Differences in the Implications of Organizational Creativity Regarding the Size of Enterprises in the Tourism Sector: The Case of Bosnia and Herzegovina - Madžar, Danijela; Milohnić, Ines; Madžar, Ivan (Academica Turistica - Tourism and Innovation Journal, 2022)
The purpose of the paper is to indicate the importance and differences in the implications of organizational creativity regarding enterprise size in the tourism sector. In the process of creativity management, it is essential to develop the capacity for continuous change and frequent adjustment while preserving the identity and value of the organization. The paper is based on a basic hypothesis that there are significant differences in managing organizational creativity associated with enterprise size in tourism. Research results have shown that larger companies are more likely to succeed in managing creativity, which is explained by their access to human, material and financial resources. In general, the behaviour of enterprises in Bosnia and Herzegovina, and especially in the tourism sector, is a relatively unexplored phenomenon. The results of the research are significant as there is no relevant research on the management of creativity in the service sector as a whole and the tourism sector of the Federation of Bosnia and Herzegovina. Keywords: management, organizational creativity, enterprise size, tourism